Long-term use of cannabis-based medicines in two children with Tourette syndrome: a case report - Woerner, Lara-Katharina; Szejko, Natalia; Fremer, Carolin; Schmitt, Simon; Müller Vahl, Kirsten R. (Frontiers in Psychiatry, 2025)
IntroductionCannabis-based medicine (CBM) is recommended for the treatment of tics in otherwise treatment-resistant adult patients with Tourette syndrome (TS). However, evidence in children with TS is very limited. Long-term effects of CBM in this population are unknown.Case presentationsWe present two cases of long-term follow-up over six and five years, respectively, in male adolescents with TS who were administered CBM starting at the age of eight and 12 years, respectively. In one patient CBM treatment was initiated with pure tetrahydrocannabinol (THC) and was later changed to current treatment with an oral THC-dominant cannabis extract (THC:cannabidiol (CBD)=25:<0.5) with a daily dose of 0.5-0.6 mL (corresponding to 12.5–15 mg THC/day). The other patient was from the beginning up to now medicated by his parents, who are physicians, with vaporized THC-dominant (24%) medicinal cannabis flowers with a dose of 0.2 g between once to thrice per day (corresponding to 48–144 mg THC/day). While in one patient, there was a moderate dose increase over the years, in the other patient dosages were adjusted individually depending on tic severity. In both patients, CBM treatment resulted in continued benefit with significant improvement of tics and psychiatric comorbidities without severe adverse effects. Academic performance of both adolescents was excellent. Neurocognitive assessments demonstrated average results in the domain of working memory and average to above average results in the domain of processing speed.ConclusionsWe present two cases of minors with TS who started CBM treatment at the age of eight and 12 years, respectively, and continued treatment for five to six years resulting in clinically relevant symptom improvement without any severe adverse effects or negative impact on cognitive and academic performance.